The hope of the second coming : - Attiken, Raj
Like most children growing up in a family with Adventist parents, I knew something about the second advent of Jesus from my childhood days. My Sabbath School teachers talked frequently about a Person who did amazing things a long time ago in a land far away. The way my Sabbath School teachers told the story, we’d get to be with him when he comes back soon, and it was an event to be anticipated with joy and delight. Although we couldn’t quite imagine what it all meant, we knew that we were special enough for him to want to come to us, so we sang with gusto: